Can platelet-rich fibrin act as a natural carrier for antibiotics delivery? A proof-of-concept study for oral surgical procedures - Francesco Bennardo; Luca Gallelli; Caterina Palleria; Manuela Colosimo; Leonzio Fortunato; Giovambattista De Sarro; Amerigo Giudice (BMC, 2023)
Abstract Objectives Evaluate the role of platelet-rich fibrin (PRF) as a natural carrier for antibiotics delivery through the analysis of drug release and antimicrobial activity. Materials and methods PRF was prepared according to the L-PRF (leukocyte- and platelet-rich fibrin) protocol. One tube was used as control (without drug), while an increasing amount of gentamicin (0.25 mg, G1; 0.5 mg, G2; 0.75 mg, G3; 1 mg, G4), linezolid (0.5 mg, L1; 1 mg, L2; 1.5 mg, L3; 2 mg, L4), vancomycin (1.25 mg, V1; 2.5 mg, V2; 3.75 mg, V3; 5 mg, V4) was added to the other tubes. At different times the supernatant was collected and analyzed. Strains of E. coli, P. aeruginosa, S. mitis, H. influenzae, S. pneumoniae, S. aureus were used to assess the antimicrobial effect of PRF membranes prepared with the same antibiotics and compared to control PRF. Results Vancomycin interfered with PRF formation. Gentamicin and linezolid did not change the physical properties of PRF and were released from membranes in the time intervals examined. The inhibition area analysis showed that control PRF had slight antibacterial activity against all tested microorganisms. Gentamicin-PRF had a massive antibacterial activity against all tested microorganisms. Results were similar for linezolid-PRF, except for its antibacterial activity against E. coli and P. aeruginosa that was comparable to control PRF. Conclusions PRF loaded with antibiotics allowed the release of antimicrobial drugs in an effective concentration. Using PRF loaded with antibiotics after oral surgery may reduce the risk of post-operative infection, replace or enhance systemic antibiotic therapy while preserving the healing properties of PRF. Further studies are needed to prove that PRF loaded with antibiotics represents a topical antibiotic delivery tool for oral surgical procedures.